Bringing back the debate on mediated and unmediated science communication: the public's perspective - Delicado, Ana (2021)
When analysing the actors of the science communication ecosystem, scholarly research has focused on the perceptions and attitudes of scientists, science journalists, and science communicators. How the public envisages the roles of science producers and mediators is mostly uncharted territory. We address this gap, by examining the results of a public consultation in Portugal concerning science communication. We show that the public demonstrates a clear preference for science communication performed by scientists, over journalists, although credibility and trust depend on multiple factors. We also ascertain that professional science communicators are mostly invisible, though the public recognises the value of ‘translators’.